Penetapan Harga Pokok dan Penerapan Full Costing Method dalam Rangka Penetapan Harga Jual - Chintya Nur Isnaini S; Arik Susbiyani; Gardina Aulin Nuha (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the calculation of the cost of goods manufactured by UD. Elza Putra in Jember and to find out the determination of the selling price of the product using a full costing approach. This research method is descriptive qualitative. The research sample is classified based on the cost of raw materials, direct labor costs, factory overhead costs and production costs. Then these costs will be calculated, and the cost of production is determined. Determination of the cost of production using the full costing method. The results showed that in determining the cost of production of UD. Elza Putra Jember obtained a result of IDR 4,842. To determine the calculation of the selling price according to the calculation of UD. Elza Putra Jember earned Rp. 8,500/pc. Meanwhile, after setting the selling price using the full costing method, the result is Rp. 6.000/pcs and according to variable costing get Rp. 8,500/pc. In conclusion, the cost of production is known to be lower than the company's method so that the company earns a profit. And the selling price according to full costing is lower than the company's method so that the company can compete with other companies that produce the same product. Keywords: Selling Price, Cost of Production, Full Costing Method